The Role of Applying the Principles of Fiscal Governance in Enhancing Fiscal Examination Mechanisms. Case Study of the Fiscal Directorate of Oum El Bouaghi District - TOUAITIA , Tahar; MAAMRI, Roumaissa (Journal of Finance & Corporate Governance, 2019)
The purpose of this study is to identify the governance system and its principles, And the extent of commitment in Tax institutions to applying their principles.To help them develop tax inspection mechanisms, To achieve the objectives of the study, a random sample of 46 members of the 50 employees of the Directorate of Taxation of Oum El Bouaghi.The study relied on the descriptive method of analysis in order to provide the theoretical basis for the study and inductive in the applied side to test the impact of applying the principles of governance in the development of tax inspection mechanisms. In this study we rely on the questionnaire tool included the first axis of the principles of governance and the second axis contains the terms of the tax inspection, according to the Likert scale five, and to test the hypotheses of the study were adopted some statistical methods such as simple regression coefficients and alpha Cronbach's coefficient .to measure the sincerity of the study, this study concluded The respondents consider that the tax institution in question is concerned with all the principles of governance because all the principles have achieved significant results.